Community-based development of agricultural activities aiming to improve dietary diversity in Western Kenya - Boedecker, J.; Termote, Céline; Kennedy, G. (2016)
This research examines the suitability of community-based participatory workshops for developing agricultural activities in order to diversify diets. The study represents the second phase of a project consisting of a diagnostic phase covering agricultural biodiversity, diets and nutrition (phase I), participatory development of community activities (phase II) and a participatory implementation of the activities (phase III). The project is part of the nutrition cross-cutting cluster work within Humidtropics, a CGIAR research programme (CRP). A series of six participatory workshops was carried out in five sub-locations of Vihiga County in Western Kenya. The workshops aimed to raise awareness on nutrition, to discuss the results of the diagnostic phase (phase I) and to identify and plan community activities to improve nutrition. Per sub-location, 36 men and women were selected to participate in the workshops. In order to diversify diets in their communities, all sub-locations decided to plant ve- getables and legumes and to raise poultry. The participants developed community action plans specifying how these activities are going to be realised. In addition, they chose local funding mechanisms to finance the actions and developed a budget. The groups also suc- ceeded in organising an event to officially kick-off their activities and thereby reaching out to other community members. Except for one less successful sub-location, the workshop groups well developed agricul- tural activities for improved nutrition. Harmony within the group was a crucial factor for good performance. Sensitivity to group dynamics is thus very important for participatory development of community activities. It was observed that the continuous workshops built trust between researchers and participants and that ownership was developed among the groups. These findings are in line with similar studies on participatory intervention deve- lopment in Africa. Other related projects in low-income countries stress the importance of community-based approaches in improving nutrition and livelihood outcomes